2020
DOI: 10.3390/agronomy10060855
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Applications Targeting Precision Agriculture Practices—A Systematic Review

Abstract: Traditionally farmers have used their perceptual sensorial systems to diagnose and monitor their crops health and needs. However, humans possess five basic perceptual systems with accuracy levels that can change from human to human which are largely dependent on the stress, experience, health and age. To overcome this problem, in the last decade, with the help of the emergence of smartphone technology, new agronomic applications were developed to reach better, cost-effective, more accurate and portable diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 34 publications
1
48
0
4
Order By: Relevance
“…In a short period of time PA approaches and practices have become very popular and were introduced in all agricultural sectors [9]. The vine and wine sector is among those that have most benefited of precision farming techniques, applied to optimise vineyard performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a short period of time PA approaches and practices have become very popular and were introduced in all agricultural sectors [9]. The vine and wine sector is among those that have most benefited of precision farming techniques, applied to optimise vineyard performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other wineries keep records of physicochemical characteristics and/or sensory profiles related to berry and wine quality traits, either done at chemistry laboratories or in-house, with some of these vineyards with records of more than 15 growing seasons. Keeping with digital technological advances, these management tools can be found in the form of computer, smartphone, and tablet PC applications for portability and easy access to records [2]. However, there have been minimal attempts to analyze these records using new and emerging tools, such as data mining and machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using consumer-class quadcopter drone with smartphone connectivity ( Figure 9 ), for in-field nucleic acid-based diagnostics, Priye et al [ 154 ] demonstrated flight replication of Staphylococcus aureus and λ-phage DNA targets in less than 20 min. Smartphone technology can also contribute to more accurate, smart, and portable diagnosis systems [ 155 , 156 ] in which connectivity, high-quality images, and processing capacity of these devices could help farmers and institutions in fighting plant diseases, all over the world. All these technologies are able to communicate to each other and open new avenues for fighting plant pathogens and their spreading, in an efficient and intuitive way.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%